Analisis Kelayakan Investasi Dalam Replanting Kopi Model Komunitas Kopista: Feasibility Analysis of Investment in Replanting Coffee Community Model Kopista - Haryono, Adi; Maarif, M. Syamsul; Suroso, Arif Imam; Jahroh, Siti (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The development of a partnership system based on contract farming can effectively address the challenges faced by farmers in boosting coffee production and subsequently improve their overall welfare.Purpose: This study aims to assess the viability of investing in replanting according to the methods of Kopista community per 2023. Design/methodology/approach: The technique analysis is a descriptive analysis of financial statements with the International Financial Accounting Standard (IFRS) approach. The study examines six key financial aspects, including production levels, operational costs, profit and loss, balance sheet, cash flow, and investment feasibility. The investment feasibility analysis employs three types of calculations, namely Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP).Findings/Result: The findings of this study demonstrate that investing in the coffee estate is a profitable venture, as it generates substantial income over a ten-year investment period. Notably, the revenue surpasses production costs, particularly during the highly productive period of coffee plants spanning from seven to twenty-five years. Consequently, implementing an investment in the new coffee estate is both viable and advisable.Conclusion: This research reveals the potential acceptance of a contract farming model designed to produce high productivity for farmers. The development of this model will have implications for improving the welfare of coffee farmers in Indonesia. The contract farming model design for replanting the Kopista method can be implemented with great support from relevant stakeholders such as banks, entrepreneurs and the government so that coffee farmers can produce more quantity compared to previous conditions.Originality/value (State of the art): This study presents coffee production methods for farmers that are proven effective and efficient through investment feasibility analysis. Keywords: coffee, feasibility, finance, Internal Rate of Return (IRR), Investment, Net Present Value (NPV), Payback Period (PP)